2008
DOI: 10.1039/b707161b
|View full text |Cite
|
Sign up to set email alerts
|

Design and evaluation of an improved microwave-based thermal nebulizer for liquid sample introduction in inductively coupled plasma atomic emission spectrometry

Abstract: A re-designed microwave-based thermal nebulizer (MWTN) that overcomes all the drawbacks shown by previous prototypes (i.e. lack of robustness, poor heating efficiency) is presented. The new device employs an optimized TM 010 cavity and nozzle design. MWTN performance was evaluated in inductively coupled plasma atomic emission spectrometry (ICP-AES) and compared to that provided by a concentric pneumatic nebulizer. Current MWTN design improves sample heating efficiency and system robustness. As a consequence, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 37 publications
0
17
0
Order By: Relevance
“…Previous results reported in the literature have shown that for both the MWTN and MWDS systems, the best analytical response is obtained when operating at high MW powers. 10,20 Due to this, the MW power used with the MASIS was fixed at the maximum available value, i.e., 290 W. In fact, it was observed that when operating at lower microwave powers, no reproducible aerosols were generated. It is interesting to note that the MW radiation power reflected in the cavity was of 40 W on average.…”
Section: Masis Characterizationmentioning
confidence: 99%
See 4 more Smart Citations
“…Previous results reported in the literature have shown that for both the MWTN and MWDS systems, the best analytical response is obtained when operating at high MW powers. 10,20 Due to this, the MW power used with the MASIS was fixed at the maximum available value, i.e., 290 W. In fact, it was observed that when operating at lower microwave powers, no reproducible aerosols were generated. It is interesting to note that the MW radiation power reflected in the cavity was of 40 W on average.…”
Section: Masis Characterizationmentioning
confidence: 99%
“…[6][7][8] Microwave radiation (MW) has also been employed as a promising alternative energy source in thermal nebulization. 9,10 Using these devices, the aerosol is generated as a consequence of the interaction between the sample vaporized inside the capillary and the remaining liquid. The aerosols generated by thermal nebulizers are finer than those produced by the conventional pneumatic ones, thus giving rise to higher plasma analyte transport rates (W tot ).…”
Section: 2mentioning
confidence: 99%
See 3 more Smart Citations